BIMG-08. DEUTERIUM MAGNETIC RESONANCE SPECTROSCOPY USING 2H-PYRUVATE ALLOWS NON-INVASIVE IN VIVO IMAGING OF TERT EXPRESSION IN BRAIN TUMORS. (25th March 2021) - Batsios, Georgios; Taglang, Celine; Tran, Meryssa; Gillespie, Anne Marie; Costello, Joseph; Ronen, Sabrina; Viswanath, Pavithra
Abstract: Telomere shortening constitutes a natural barrier to uncontrolled proliferation and all tumors must find a mechanism of maintaining telomere length. Most human tumors, including high-grade primary glioblastomas (GBMs) and low-grade oligodendrogliomas (LGOGs) achieve telomere maintenance via reactivation of the expression of telomerase reverse transcriptase (TERT), which is silenced in normal somatic cells. TERT expression is, therefore, a driver of tumor proliferation and, due to this essential role, TERT is also a therapeutic target. However, non-invasive methods of imaging TERT are lacking. The goal of this study was to identify magnetic resonance spectroscopy (MRS)-detectable metabolic biomarkers of TERT expression that will enable non-invasive visualization of tumor burden in LGOGs and GBMs. First, we silenced TERT expression by RNA interference in patient-derived LGOG (SF10417, BT88) and GBM (GS2) models. Our results linked TERT silencing to significant reductions in steady-state levels of NADH in all models. NADH is essential for the conversion of pyruvate to lactate, suggesting that measuring pyruvate flux to lactate could be useful for imaging TERT status. Recently, deuterium ( 2 H)-MRS has emerged as a novel, clinically translatable method of monitoring metabolic fluxes in vivo . However, to date, studies have solely examined 2 H-glucose and the use of [U- 2 H]pyruvate for non-invasive 2 H-MRS has not been tested. Following intravenous injection of a bolus of [U- 2 H]pyruvate, lactate production was higher in mice bearing orthotopic LGOG (BT88 and SF10417) and GBM (GS2) tumor xenografts relative to tumor-free mice, suggesting that [U- 2 H]pyruvate has the potential to monitor TERT expression in vivo . In summary, our study, for the first time, shows the feasibility and utility of [U- 2 H]pyruvate for in vivo imaging. Importantly, since 2 H-MRS can be implemented on clinical scanners, our results provide a novel, non-invasive method of integrating information regarding a fundamental cancer hallmark, i.e. TERT, into glioma patient management.